Pemanfaatan Limbah Organik Tulang Ayam dan Sisa Nasi Sebagai Pakan Larva Lalat Tentara Hitam (Hermetia illucens L.) - Eunike Dian Swastoko; Kukuh Madyaningrana; Krismono Krismono (Biotropic : The Journal of Tropical Biology, 2023)
Organic waste originating from restaurants brings problems to the environment because it can cause bad smells and environmental pollution. To reduce this pollution, organic waste can be decomposed and used as feed for black soldier fly (BSF) larvae can be useful as fish or poultry feed with high nutrition. Therefore, this research aimed to determine and study the feeding of organic waste, namely leftover rice and chicken bones, on the growth of BSF larvae. The resesearch was conducted using a completely randomized design (CRD) with 3 feeding treatments consist of leftover rice, chicken bones, and combination of leftover rice and chicken bones; and control treatment used T-51 pig feed. All teratments used triplicates. Data obtained from this study consist of BSF larvae growth parameter for 12 days, and proximate analysis of the feed and BSF larvae. Results showed that larvae fed with a combination of leftover rice and chicken bones was the best treatment to support the groeth of BSF larvae as shown by values of waste reduction index (WRI) 0,034 g/day, substrate reduction 51%, and 98 % of BSF larvae survival rate 98% in 12 days.